PENGARUH NAUNGAN DAN INTERVAL POTONG TERHADAP PRODUKSI HIJAUAN Arachis pintoi - Fanindi, Achmad; Sutedi, Endang; Sajimin, Sajimin (Pastura, 2011)
Arachis pintoi is the forage that has multiple functions like improving soil fertility, preventing soil erosion, as well as for feed and shade tolerance. A research has been conducted at Reasearch Institute of Animal Production for one year in order to study the effect of shading and cutting interval on forage production of Arachispintoi. The shade was made of paranet, Arachispintoi were planted using pols in pots with a diameter of 36 cm. Pots were placed on the artificial shade 2,5 x 2,5 m wich each side was covered with a shade appropriate treatment. Shade to the plant height of two meter. A factorial randomized block design was arranged with three replications, as the first factor was the intensity of shading which consists of: N0 = Control without shade, N1 = Shade using 1 layer paranet (50% shade), N2 = Shade using 2 layers of paranet (70% shade), N3 = Shade using 3 layers of paranet (80% shade), N4 = Shade using 4 layer paranet (90% shade), as a second factor was the cutting interval which consisted of: the interval 1 month, 2 months, 3 months and 4 months. The results showed that the level of shading and cutting interval effect highly significant (P <0.01) on forage production of freshand dry weight of Arachis pintoi. Until at the 50% shade level (N1) the production of forage Arachis pintoi did not significantly different compared to the production of forage Arachis without shade. While cutting interval of 3 month showed higher production when compared with Arachis production cut at intervals of 1, 2 and 4 months.
Keywords: Arachis pintoi; shade; cutting interval; production